1991
DOI: 10.1093/oxfordjournals.humrep.a137445
|View full text |Cite
|
Sign up to set email alerts
|

Secretory endometrial protein PP14 in women with early pregnancy bleeding

Abstract: The decidualized endometrium produces secretory proteins of which secretory endometrial protein PP14 is the major product during the first trimester of pregnancy. The protein is secreted into the uterine lumen as well as into the peripheral blood. The purpose of this study was to examine whether decidual function, evaluated by the serum concentration of PP14, was different in women with early pregnancy bleeding compared to normal pregnant women. A reference range for serum PP14 was established on the basis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Since PP14 is the major secretory protein of the endometrium in the early first trimester of pregnancy, circulating PP14 levels might reflect events at the site of implantation, together with the viability and outcome of the pregnancy. The present study, as that of Ruge et al (1991) demonstrates that threatened miscarriage is not associated with depressed PP14 levels, irrespective of whether the fetus is alive and the pregnancy continues to term, or is destined to subsequently miscarry, or is absent (as with an anembryonic or molar pregnancy) or even dead (as in missed miscarriage).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Since PP14 is the major secretory protein of the endometrium in the early first trimester of pregnancy, circulating PP14 levels might reflect events at the site of implantation, together with the viability and outcome of the pregnancy. The present study, as that of Ruge et al (1991) demonstrates that threatened miscarriage is not associated with depressed PP14 levels, irrespective of whether the fetus is alive and the pregnancy continues to term, or is destined to subsequently miscarry, or is absent (as with an anembryonic or molar pregnancy) or even dead (as in missed miscarriage).…”
Section: Discussionsupporting
confidence: 49%
“…It has been postulated that PP14 may be a clinical marker of the activity of the glandular epithelium of the endometrium during implantation and placentation (Bell et al 1985; Chard & Olajide 1994). Previous work has demonstrated that threatened miscarriage is not associated with depressed PP14 levels (Ruge et al 1991). However, Ruge et al (1992) demonstrated low serum PP14 and progesterone levels in 59 women with ectopic pregnancy.…”
mentioning
confidence: 95%
“…hPL was measured by a commercially available radioimmunoassay (Phadebas A , Pharmacia, Uppsala, Sweden). Locally established radioimmunoassays were used to determine PAPP-A and PP14 (6,7).…”
Section: Methodsmentioning
confidence: 99%
“…Early-pregnancy bleeding, ectopic pregnancy. Serum glycodelin concentration has been used to evaluate whether decidual function is different in women with early-pregnancy bleeding compared with normal pregnant women (187). A reference range for serum glycodelin concentrations was established on the basis of single samples from 236 women with normal pregnancy in whom gestational age was ultrasonically confirmed.…”
Section: Pregnancy Termination and Disordersmentioning
confidence: 99%